MOLLUSCICIDAL ACTIVITY OF CERTAIN SUDANESE MEDICINAL PLANTS USED IN FOLK – MEDICINE - M.Ahmed, El-Hadi M.; Elsubki, Hassan; Gamar, Yousif (Gezira Journal of Health Sciences, 2005)
Objectives: In view of the promising potential of plant molluscicides, 10 plants indigenous to Sudan and of common use in Sudanese folk-medicine, were screened for their molluscicidal activity, using two local snail vectors, Bulinus truncates and Biomphalaria pfeifferi . Results: At different concentrations up to 500 ppm., seven plant samples were found to be lethal to both of the snail species. The pet. ether/CHCH 3 (1:1) extracts of 6 plants were lethal as molluscicidal agents while only two plants showed 100% mortality to the snails as methanol extracts. The two most active plants that killed both snail hosts ( ≤ 50 ppm.), were obtained from the whole plant of Ambrosia maritimae (Asteraceae) and the fruits of Croton zambesicus (Euphorbiaceae). These two plants when phytochemically screened for their active constituents, they showed the presence of sterols and cardenolides. Conclusion: Vegetable molluscicides can be grown and can be used by communities in endemic areas to combat schistosomiasis